Cultural diversity in textbooks and children's literature in Italy (1980-2000). Breakthrough or continuity? - Maria Lucenti (University of Bologna, 2022)
The paper intends to study the construction of the childhood imagination on diversity starting from two different sources and narratives, aware of the fact that they have equally contributed to picturing and shaping ideas and images of one other on young minds. The contribution's main aim is to highlight how cultural diversity has been represented in formal and informal education, through the analysis of textbooks and children's literature. To this end, Italian textbooks and novels published from the 1980s to 2000 have been selected in order to retrace cultural changes at a historical level and how both school and children's literature have responded to the challenges of an increasingly culturally heterogeneous society. The analysis showed that while the best children's literature offers alternatives and intercultural models to the young readers who know how to recognize and choose a good story establishing a rupture with the representations conveyed in the texts and novels of previous decades. Textbooks, for their part, are placed in continuity, they are slow to recognise and value cultural diversity.